PENGARUH LEVERAGE, LIKUIDITAS, MARKET TO BOOK VALUE, FINANCIAL DISTRESS, DAN FIRM SIZE TERHADAP KEPUTUSAN HEDGING (STUDI PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRI PERIODE 2011-2016) - TRI ADITYA, ANGGA; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2018)
Hedging is a policy that can be carried out by multinantional companies to minimize the risk of foreign exchange faced. The purpose of this study is to determine the effect of leverage, liquidity, market to book value, financial distress, and firm size on hedging decisions on consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2011-2016. This type of research is a quantitative in the from of causality by using purposive sampling methods, so that obtained 24 companies that meet the criteria. Statistical analysis used in this study is SPSS. The technical analysis used in this study is logistic regression analysis. The results shows that leverage proxied by debt equity ratio, market to book value which is calculated using the comparison of market value and book value, and the firm size which is obtained from the total assets loan does not effect hedging decisions. The liquidity proxied by the current ratio has a significant negative effect on hedging decisions, the last is, financial distress which is calculated using the formula from Altman Z-Score has a significant positive effect on hedging decisions. Keywords: financial distress; firm size; hedging; leverage; liquidity; market to book value